ETHNOBOTANICAL STUDY AND CONSERVATION STATUS OF LOCAL MEDICINAL PLANTS: TOWARDS A REPOSITORY AND MONOGRAPH OF HERBAL MEDICINES IN LESOTHO - Mugomeri, Eltony; Chatanga, Peter; Raditladi, Tirelo; Makara, ‘Mopane; Tarirai, Clemence (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Plants are important sources of medicines. Herbal medicines in Lesotho are exposed to excessive exploitation and habitat destruction. Comprehensive information to promote proper use and conservation of these herbal medicines is lacking. This study described the uses of medicinal plants in Lesotho with comparative reference between practice and the literature, highlighting important ethno-medicinal information and conservation status of the plants. Additionally, the study established a repository and monograph for the herbal medicines in Lesotho. Materials and Methods: Medicinal plant samples and information on their uses were obtained from herbalists in four districts of Lesotho between January and May 2014 through questionnaire-based interviews. Samples consisted of roots, bark, stems or leaves and/or combinations. Voucher samples were processed into powders, labelled, and stored in a repository. Information on the uses, plant parts used, geographical distribution, known phytochemical components and conservation status of each plant was recorded in a Microsoft Access database. Results: Seventy-eight local herbalists were interviewed and men (about 84%) dominated the practice of traditional medicine. Fifty-four herbal medicine samples were collected and stored in a recently established Lesotho Herbal Medicines Repository (LHMR). The herbal medicines were from 54 medicinal plant species and 46 genera belonging to 29 plant families. Asteraceae (about 20%) was the most common plant family. Overall, 46% (n=54) of the prescriptions by local herbalists were similar to prescriptions in the literature at least in part. However, traditional medicinal uses for 9% of the plant samples could not be confirmed from the literature. Local herbalists use different parts of medicinal plants with roots being the most frequently (57%) used part. Twenty percent of the plants were threatened with extinction while the conservation status of 7% of the plants was undocumented. Conclusion: Training of local herbalists on sustainable harvesting and safe use of medicinal plants is recommended. The repository and monograph is a useful reference and source of herbal medicine samples for researchers, which need to be expanded to include more medicinal plants in Lesotho. Local herbalists in Lesotho have valuable indigenous information on medicinal plants that needs to be documented.